Subcutaneous bortezomib-containing regimens as up-front treatment of newly diagnosed transplant-eligible multiple myeloma patients: a retrospective, non-interventional observational study. Issue 8 (3rd July 2021) - Rizzello, Ilaria; Cavo, Michele; Dozza, Luca; Rivolti, Elena; Petrucci, Maria Teresa; De Stefano, Valerio; Antonioli, Elisabetta; Tosi, Patrizia; D'Agostino, Mattia; Morè, Sonia; Gozzetti, Alessandro; Cea, Michele; et al.
Abstract: Subcutaneous (SC) bortezomib-based regimens represent the standard induction therapy prior to autologous stem cell transplantation (ASCT) in newly diagnosed multiple myeloma patients. Published data are based principally on intravenous (IV) administration: this retrospective observational study aimed to define patients' outcomes upon SC bortezomib administration, before and after ASCT. Of 131 enrolled patients, 86% received bortezomib-dexamethasone plus thalidomide (VTD), 5% plus cyclophosphamide (VCD), and 9% alone (VD), for a median of 4 cycles induction therapy, followed by single (52%) or double (48%) ASCT. 48 patients received consolidation with the same induction regimen. 35% had at least one adverse event, mainly gastrointestinal disorders and peripheral neuropathy (PN). ORR was 93.1%, 97.7% and 100%, after induction, ASCT(s) and consolidation, respectively. Median PFS and PFS2 were 55.8 months and 72 months, respectively, (median follow-up 45.3 months), while median OS was unreached. Concluding, SC bortezomib has similar efficacy with reduced PN than IV administration.